Konseptualisasi Nilai-Nilai Moral dalam Perspektif Islam - Khoirul Umam Addzaky; Clara Apriyanti (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
In the modern era, moral education has become increasingly important as rapid developments in science and technology, coupled with globalization, have brought significant value changes in society. This study examines the Islamic perspective on moral values (akhlaq) and their fundamental role in Islamic education. Using a qualitative library research approach, this study analyzes primary Islamic sources including the Quran and Hadith, along with classical and contemporary Islamic scholarship on moral philosophy. The research explores the ontological, epistemological, and axiological dimensions of moral values in Islam, examining how Islamic moral principles are derived, understood, and applied. The findings reveal that Islamic moral values are grounded in divine revelation, characterized by their absolute, universal, and objective nature. The study demonstrates that moral education in Islam aims to develop insan kamil (perfect human beings) who embody noble character traits while avoiding reprehensible qualities. Classical Islamic philosophers such as Al-Ghazali, Al-Farabi, and Ibn Miskawaih contributed significantly to moral philosophy, emphasizing the connection between morality and human happiness. The research concludes that Islamic moral values serve as a comprehensive guide for human conduct, providing both worldly and spiritual guidance that remains relevant in contemporary contexts.